Determination of Carbendazim and Diethofencarb in Cotton and Soil by High-Performance Liquid Chromatography. (2nd July 2016) - Qin, Xu; Xu, Yingming; Sun, Yang; Zhao, Lijie; Wang, Lin; Sun, Yuebing; Liang, Xuefeng
ABSTRACT: A simple and reliable method was developed to determine carbendazim and diethofencarb in cotton, cotton seeds, and soil. The decomposition of carbendazim and diethofencarb in the cotton field ecosystem was also studied. The analytes were extracted and quantified by high-performance liquid chromatography. The limits of detection were 0.1 ng for carbendazim and diethofencarb. The limits of quantification of carbendazim and diethofencarb were 0.1 mg kg −1 in cotton, 0.1 mg kg −1 in cotton seeds, and 0.02 mg kg −1 in soil. The average recoveries of cotton, cotton seed, and soil were measured at three fortified concentrations and were in the range of 77.5–103.9% for carbendazim and 80.9–104.6% for diethofencarb. The relative standard deviations were less than 9.0% for both pesticides. In field experiments, the half-lives of carbendazim and diethofencarb were in the range of 2.3–9.1 days and 2.3–8.9 days in cotton at two locations in China. At harvest, cotton seeds contained carbendazim and diethofencarb well below the maximum residue limit of the Japanese "Positive List System" (3 mg kg −1 ) following the recommended dosage with measurement 10 and 20 days following the final application.